2021
DOI: 10.3390/plants11010055
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Potassium Supply under Osmotic Stress Mitigates Oxidative Damage in Barley

Abstract: Potassium (K) is the most abundant cation in plants, playing an important role in osmoregulation. Little is known about the effect of genotypic variation in the tolerance to osmotic stress under different K treatments in barley. In this study, we measured the interactive effects of osmotic stress and K supply on growth and stress responses of two barley cultivars (Hordeum vulgare L.) and monitored reactive oxygen species (ROS) along with enzymatic antioxidant activity and their respective gene expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Thus, we suggest that the high accumulation of proline and K in shoots participates in maintaining leaf hydration, key metabolic reactions (photosynthesis …), and plant growth. This suggestion is confirmed by the results of Tavakol et al [ 33 ], who reported that K is the most abundant cation in plants, playing an important role in osmoregulation. When drought stress occurs, the availability of plant nutrients is decisive in plant stress adaptation and avoidance.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, we suggest that the high accumulation of proline and K in shoots participates in maintaining leaf hydration, key metabolic reactions (photosynthesis …), and plant growth. This suggestion is confirmed by the results of Tavakol et al [ 33 ], who reported that K is the most abundant cation in plants, playing an important role in osmoregulation. When drought stress occurs, the availability of plant nutrients is decisive in plant stress adaptation and avoidance.…”
Section: Discussionsupporting
confidence: 81%
“…Potassium is the most abundant cation in plants and affects the osmotic potential of plant cells, consequently playing a crucial role in stress mitigation [ 30 ]. Adequate K availability under osmotic stress improves plant water uptake, and water use efficiency decreases the ABA content, and avoids limitations in stomatal conductance and assimilation [ 33 , 55 , 56 ]. Otherwise, Chowdhury et al [ 36 ] reported higher capacities of proline accumulation in the tolerant genotypes of wheat, BAW1158 and BAW 1169, subjected to drought stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, long-term exposure to water deficit conditions led to leaf damage due to ROS formation (Wang et al, 2013). In support of this, optimization of K + supply mitigates the damage caused due to the oxidative stress in barley exposed to drought stress (Tavakol et al, 2021). Silencing HvAKT2 and HvHAK1 in barley enhanced the ROS (H 2 O 2 ) production in PEG-treated leaves (Feng et al, 2020a).…”
Section: Evolutionary Divergence and Comparative Analysismentioning
confidence: 95%
“…A fresh leaf sample (0.3 g) was homogenized in 5 ml of 50 mM of phosphate buffer (pH 7.0) and 10 g L −1 of polyvinylpyrrolidone and centrifuged at 15,000×g for 20 min, and then the supernatants were collected as a crude extraction for enzyme activity determinations. 1) SOD (EC 1.15.1.1) activity was determined by monitoring the inhibition of photochemical reduction of Nitro blue tetrazolium (NBT) according to Tavakol et al (2021). 2) CAT (EC 1.11.1.6) activity was measured by the ammonium molybdate method (Djanaguiraman et al, 2009).…”
Section: Antioxidant Enzyme Extraction and Analysismentioning
confidence: 99%